2020
DOI: 10.3390/molecules25061332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inclusion of Fresh Forage in the Diet for Lactating Buffaloes on Volatile Organic Compounds of Milk and Mozzarella Cheese

Abstract: This paper aimed to assess the effects of feeding fresh forage on volatile organic compounds (VOCs) of buffalo milk and mozzarella cheese. Sixteen lactating buffaloes were equally allotted into two groups fed diets containing (experimental (Exp) group) or not (control (Ctl) group) 20 kg/d of fresh sorghum. Milk from the groups was separately collected and transformed in the traditional ‘Mozzarella di Bufala Campana’ Protected Denomination of Origin (PDO). Three batches of mozzarella were produced for each diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
3
21
1
Order By: Relevance
“…It is likely that they derive from the qualitative and quantitative differences in the microbiological profile of the milk samples. Contrary to what observed for milk, the results obtained in cheese were different from those reported by Sacchi et al (2020) in buffalo mozzarella. Besides being the consequence of the different type of milk used, the differences could also derive from the different acidification techniques.…”
Section: Curd and Mozzarellacontrasting
confidence: 99%
See 2 more Smart Citations
“…It is likely that they derive from the qualitative and quantitative differences in the microbiological profile of the milk samples. Contrary to what observed for milk, the results obtained in cheese were different from those reported by Sacchi et al (2020) in buffalo mozzarella. Besides being the consequence of the different type of milk used, the differences could also derive from the different acidification techniques.…”
Section: Curd and Mozzarellacontrasting
confidence: 99%
“…The results obtained are almost identical to those reported by Sacchi et al . (2020) in a similar research on buffalo milk that also considered the effect of inclusion of fresh forage in the diet. Figure 2 shows PLS‐DA of EXT milk samples in connection with the type of grass available to cows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This thermal treatment may at least partly reduce the activity of the odor compounds in the milk obtained from grazing animals thus flattening the odor profile of the corresponding cheese. Accordingly, it has been recently observed that the amount of volatile organic compounds of milk may be markedly reduced in mozzarella, due to the high temperatures of curd during stretching [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both Bagnolese pecorino and Cantal are semi-cooked cheeses produced from raw milk so that neither milk nor curd are subjected to temperatures higher than 50 • C. By contrast, during pasta filata cheese making, the curd is stretched in water or whey heated at 80-90 • C. This thermal treatment may at least partly reduce the activity of the odor compounds in the milk obtained from grazing animals thus flattening the odor profile of the corresponding cheese. Accordingly, it has been recently observed that the amount of volatile organic compounds of milk may be markedly reduced in mozzarella, due to the high temperatures of curd during stretching [66].…”
Section: Cheese Sensory Properties and Consumer Likingmentioning
confidence: 99%